Structure of the SigE regulatory network in Mycobacterium tuberculosis - Cioetto-Mazzabò, Laura; Sorze, Davide; Babic, Fedora; Boldrin, Francesca; Segafreddo, Greta; Provvedi, Roberta; Manganelli, Riccardo (Frontiers in Microbiology, 2024)
SigE is one of the main regulators of mycobacterial stress response and is characterized by a complex regulatory network based on two pathways, which have been partially characterized in conditions of surface stress. The first pathway is based on the induction of sigE transcription by the two-component system MprAB, while the second is based on the degradation of SigE anti-sigma factor RseA by ClpC1P2, a protease whose structural genes are induced by ClgR. We characterized the dynamics of the SigE network activation in conditions of surface stress and low pH in Mycobacterium tuberculosis.Using a series of mutants in which the main regulatory nodes of the network have been inactivated, we could explore their hierarchy, and we determined that MprAB had a key role in the network activation in both stress conditions through the induction of sigE. However, while in conditions of surface stress the absence of MprAB totally abrogated sigE induction, under low pH conditions it only resulted in a small delay of the induction of sigE. In this case, sigE induction was due to SigH, which acted as a MprAB backup system. The ClgR pathway, leading to the degradation of the SigE anti-sigma factor RseA, was shown to be essential for the activation of the SigE network only following surface stress, where it showed an equal hierarchy with the MprAB pathway.